Percepção e uso dos solos: o caso dos agricultores familiares da Região Centro-Sul do Paraná - Benassi, Dacio Antonio (2008)
Etnopedological studies in different environmental and socioeconomic contexts can contribute to the improvement of the technical knowledge and for a better understanding of the local knowledge systems, soil use and management. This research aimed at to assess the soil knowledge of a group of family farmers at two rural communities located at the municipality of Irati, Central-Southern Paraná, as well as to understand how this knowledge is used for agricultural production. The local pedologic knowledge was described and analyzed using participatory methodologies. Semi-structured questionnaires, maps, discussions at soil profile and matrix ranking techniques were applied to a group of 30 farmers in order to assess the level of knowledge on soils (emic approach). Then the soil types identified by the farmers were described using the technical knowledge (etic approach). It was conclude that farmers established a soil typology based on a classification system of regional breadth. Eight soil types were identified: 1) “Terra Branca Batumadeira”; 2) “Saibro Azul”; 3) “Saibrinho Amarelo”; 4) “Terra Amarela”; 5) “Terra Preta do Cerro da Ponte Alta”; 6) “Terra Preta da Barra Mansa”; 7) “Terra Branca Solta”; e, 8) “Terra de Areia”. In the formal soil system classification, three types of soils had been identified: “CAMBISSOLO HÁPLICO”, “NEOSSOLO LITÓLICO Eutrófico típico” and “NEOSSOLO LITÓLICO Distrófico Típico”. The results had demonstrated that the agriculturists had obtained to discriminate a number bigger of ground classrooms, allowing bigger detailing of units of ground in the landscape. The pedological knowledge of local farmers can complement local scientific knowledge of soils and contribute with the accomplishment of mappings detailed in the small familiar properties, to a lesser cost and with lesser great expense of tim.